2013
DOI: 10.3892/etm.2013.1201
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow stromal cells inhibit caspase-12 expression in rats with spinal cord injury

Abstract: The mechanisms underlying the potentially beneficial effect of bone marrow stem cells (BMSCs) on spinal cord injury (SCI) are unknown. Therefore, the aim of the present study was to explore the protective effect of BMSCs in rats with SCI. A total of 45 adult male Sprague-Dawley rats were randomly divided into three groups; the SCI group (n=15), the BMSC group (n=15) and the sham-operation group (n=15). In the SCI and BMSC treatment groups, a modified Allen’s weight-drop technique was used to induce SCI. The BM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…This demonstrated that the attenuation of caspase-12 expression, in part, protects against endothelial dysfunction, however other important pathways seem to be involved in the beneficial effect CM has on vascular grafts of aged rats. It has been shown that bone marrow stromal cell therapy inhibits the expression of caspase-12 in rats with ischemic spinal cord injury [ 30 ]. It has also been demonstrated that activin A inhibited ER stress-induced apoptotic and autophagic cell death [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…This demonstrated that the attenuation of caspase-12 expression, in part, protects against endothelial dysfunction, however other important pathways seem to be involved in the beneficial effect CM has on vascular grafts of aged rats. It has been shown that bone marrow stromal cell therapy inhibits the expression of caspase-12 in rats with ischemic spinal cord injury [ 30 ]. It has also been demonstrated that activin A inhibited ER stress-induced apoptotic and autophagic cell death [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…All efforts were made to minimize the number of animals used and their suffering. BMSCs were isolated from 3 to 4 week old Sprague-Dawley male rats according to our previous study 4, 26. BMSCs were cultured in Dulbecco's modified Eagle's medium (DMEM) with 10% fetal bovine serum (FBS, Gibco, USA) and 1% penicillin and streptomycin (Gibco, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies demonstrated that BMSCs could protect injured neurons and prevent neuronal apoptosis after SCI 26, 27. Thus, we hypothesized that transfer of mitochondria from BMSCs to the injured neurons might play an important role in the protective effects of BMSCs on SCI.…”
Section: Introductionmentioning
confidence: 95%
“…A mechanism of action based on downregulating the activity of caspase-3 has been reported for neural precursor cells [ 59 ], human amniotic mesenchymal stem cells [ 74 ], and rat bone-marrow-mesenchymal cells [ 75 ] transplanted in rodent SCI models. MSCs have been shown to downregulate caspase-12 [ 76 ] and caspase-9 expression, and the largest effect was obtained when co-transplanted with olfactory ensheathing cells [ 77 ]. Apoptosis could be inhibited by MSCs directly [ 75 , 78 ], by administration together with selected pharmaceuticals [ 79 ], co-transplantation with olfactory ensheathing cells [ 77 ], or by their secretome, which was evidenced by the administration of MSC-derived extracellular vesicles into the injured spinal cord [ 80 ].…”
Section: Keeping a Balance Between Neuronal Apoptosis And Autophagymentioning
confidence: 99%